Cure kinetics of acrylated epoxidized hemp oil-based bioresin system - Francucci, Gaston Martin (2012)
In this work, the cure kinetics of a novel acrylated epoxidized hemp oil (AEHO)-based bioresin was investigated for the first time by differential scanning calorimetry (DSC) using both isothermal and nonisothermal conditions. This new bioresin was synthesized by the acrylation of a previously epoxidized hemp oil (EHO) bioresin. The curing of the AEHO bioresin showed an autocatalytic behavior with the vitrification phenomenon preventing the conversion reaching unity for all the temperatures studied. It was found that the curing behavior can be modeled with high accuracy using a modified Kamal autocatalytic model that takes into account the vitrification phenomenon. Dynamic activation energies were determined from the Kissinger and Ozawa–Flynn–Wall methods, resulting in 58.87 and 62.02 kJmol−1, respectively. In addition, activation energies associated with the autocatalytic model constants, k1 and k2, were established to be equal to 58.94 and 45.32 kJmol−1, respectively.